2013
DOI: 10.1111/1753-6405.12077
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections, sexual risk behaviours and perceived barriers to safe sex among drug users

Abstract: Periodic assessments of alcohol use, and brief interventions for drug users who report problematic use, should also be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…As illiteracy was known to be a risk factor for HCV transmission in Egypt, the endorsement of health education about the usage of single-use syringes, screening, and treatment of the diagnosed patients decreased the transmission rate and HCV-related complications[ 49 ]. Education program directed to awareness about infection risks due to having sex with multiple partner and IV drug use, and precautions to reduce infection transmission by single needle use and cleaning the injection site[ 50 , 51 ].…”
Section: Community-based Participation In Hcv Battlementioning
confidence: 99%
“…As illiteracy was known to be a risk factor for HCV transmission in Egypt, the endorsement of health education about the usage of single-use syringes, screening, and treatment of the diagnosed patients decreased the transmission rate and HCV-related complications[ 49 ]. Education program directed to awareness about infection risks due to having sex with multiple partner and IV drug use, and precautions to reduce infection transmission by single needle use and cleaning the injection site[ 50 , 51 ].…”
Section: Community-based Participation In Hcv Battlementioning
confidence: 99%
“…People living with HIV have a greater relative risk for cardiovascular disease and other medical comorbidities, and this frequency increases with age (Islam et al 2013; Kendall et al 2014). HIV+ individuals with cerebrovascular risk have increased cognitive difficulties (Foley et al 2010; Nakamoto et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that an intersection between higher rates of risky sexual behaviors such as unprotected sex, multiple sex partners, and drug use (Blankenship, Reinhard, & El-Bassel, 2015; Dyer et al, 2013; El-Bassel & Strathdee, 2015; Islam et al, 2013; Chorba et al, 2012; McHugh et al, 2012; Patrick et al, 2012; Shoptow et al, 2014). Specifically, the rates of prescription drugs used non-medically are rising, now becoming one of the leading substance used (Dunn et al, 2013; Benotsch et al, 2011; Lankenau et al, 2012; Mackey, Liang, & Strathdee, 2013).…”
Section: Introductionmentioning
confidence: 99%